AIR DALAM PANDANGAN SAINS DAN AL-QUR’AN - Lutfi, Chairul; Zulfiqri, Muammar (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2023)
Water has a central role in life according to the view of the Koran. Water is a gift from God that is vital for life. The scientific miracle of the Qur'an is also manifested through the statement that all living things are composed of water, in accordance with modern biological findings which show that 80% of the cytoplasmic material of cells consists of water. The Qur'an's view of rainwater reflects the miracle of balanced natural cycles, the amount of rain that falls on the earth is constant, around 16 tonnes of water is estimated to evaporate every second. This is interpreted as a sign of the water cycle regulated by Allah. From a scientific perspective, water has a crucial role in cell formation and biological processes, being the main prerequisite for the function of human organs. Both from a religious and scientific perspective, it is proven that the urgency of water is in maintaining the sustainability of life and the function of the human body. In line with biological principles, the Qur'anic view provides inter